Rancang Bangun Sistem Monitoring Temperatur Dan Kelembapan Berbasis Internet of Things Untuk Rantai Dingin Penyimpanan Vaksin - Utami Nuri Adilah; Aurellia Hendrawan; Muhammad Arman; Nur Khakim; Rofan Aziz (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Temperature and humidity monitoring are important aspects of the cold chain vaccine storage system for preserving quality. Manual temperature recording risks missing readings, which compromise the vaccine quality. Excessive humidity may cause condensation on packaging, while very low humidity can reduce the stability of certain vaccines. This research aimed to design and build an Internet of Things (IoT) monitoring system with real-time notifications and website integration to support the vaccine storage cold chain system. The system used an ESP32 microcontroller, an SHT31 sensor, and dual storage (Firebase and SD Card). Development utilized Arduino IDE, Next.js framework, Telegram bot, Firebase, and Visual Studio Code editor. Tests included accuracy measurement, received signal strength indicator (RSSI) measurement, notification and data monitoring for several days. Performance was tested in Bio Farma's cold room, freezer, and walk-in cooler at Politeknik Negeri Bandung to represent various vaccine storage conditions. The results show that the system records data in real-time with a high level of accuracy (temperature error <1%, RH ±15%), low data loss (6 out of 426 data in 10 days), and operating endurance of ±3 hours. Tests proved the system to be an accurate, automated monitoring system for the cold chain vaccine storage.